Trends in the nephrologist workforce in South Africa (2002-2017) and forecasting for 2030. - Dominic Dzamesi Kumashie (Public Library of Science (PLoS), 2021)
Background The growing global health burden of kidney disease is substantial and the nephrology workforce is critical to managing it. There are concerns that the nephrology workforce appears to be shrinking in many countries. This study analyses trends in South Africa for the period 2002-2017, describes current training capacity and uses this as a basis for forecasting the nephrology workforce for 2030. Methods Data on registered nephrologists for the period 2002 to 2017 was obtained from the Health Professions Council of South Africa and the Colleges of Medicine of South Africa. Training capacity was assessed using data on government-funded posts for nephrologists and nephrology trainees, as well as training post numbers (the latter reflecting potential training capacity). Based on the trends, the gap in the supply of nephrologists was forecast for 2030 based on three targets: reducing the inequalities in provincial nephrologist densities, reducing the gap between public and private sector nephrologist densities, and international benchmarking using the Global Kidney Health Atlas and British Renal Society recommendations. Results The number of nephrologists increased from 53 to 141 (paediatric nephrologists increased from 9 to 22) over the period 2002-2017. The density in 2017 was 2.5 nephrologists per million population (pmp). In 2002, the median age of nephrologists was 46 years (interquartile range (IQR) 39-56 years) and in 2017 the median age was 48 years (IQR 41-56 years). The number of female nephrologists increased from 4 to 43 and the number of Black nephrologists increased from 3 to 24. There have been no nephrologists practising in the North West and Mpumalanga provinces and only one each in Limpopo and the Northern Cape. The current rate of production of nephrologists is eight per year. At this rate, and considering estimates of nephrologists exiting the workforce, there will be 2.6 nephrologists pmp in 2030. There are 17 government-funded nephrology trainee posts while the potential number based on the prescribed trainer-trainee ratio is 72. To increase the nephrologist density of all provinces to at least the level of KwaZulu-Natal (2.8 pmp), which has a density closest to the country average, a projected 72 additional nephrologists (six per year) would be needed by 2030. Benchmarking against the 25th centile (5.1 pmp) of upper-middle-income countries (UMICs) reported in the Global Kidney Health Atlas would require the training of an additional eight nephrologists per year. Conclusions South Africa has insufficient nephrologists, especially in the public sector and in certain provinces. A substantial increase in the production of new nephrologists is required. This requires an increase in funded training posts and posts for qualified nephrologists in the public sector. This study has estimated the numbers and distribution of nephrologists needed to address provincial inequalities and achieve realistic nephrologist density targets.